The Effect of Organizational Citizenship Behaviour on Public Service Motivation: An Analytical Research in The Companies Registration Department at The Ministry of Trade - Kamil Ezzi Al- Bayati*, Samar; Hasson Al-Taie, Ali (Journal of Economics and Administrative Sciences, 2024)
This study aims to test the influence of organizational citizenship behaviour (OCB) as an independent variable on public service motivation (PSM) as a dependent variable within the Companies Registration Department, a subsidiary of the Ministry of Trade. Data collection encompassed responses from 140 participants, spanning departmental managers, section heads, unit leaders, and staff members, obtained through a comprehensive questionnaire. The ensuing data analysis employed a descriptive-analytical approach, incorporating various statistical methodologies, such as mean computation, standard deviation, simple linear regression, and others, facilitated by statistical software packages such as (SPSS). Contrary to initial expectations, the research results negate the hypotheses and indicate a statistically significant relationship between these variables, as organizational citizenship behaviour positively affects public service motivation.Paper type: Research paper